SOURCES AND MEANS OF FORMING THE NATIONAL PRIDE OF THE UZBEK PEOPLE IN THE CONDITIONS OF MODERNIZING UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
This article reveals that the years of independence are the main task of restoring the national pride of our people, renewal and spiritual improvement of our society. We understand well that at the present stage of development of New Uzbekistan, along with social, economic and political factors, reforms implemented in the spiritual and educational aspects are also important. From this point of view, this article explores the relevance of the scientific study of theoretical and practical issues related to the restoration and education of the national pride of our people today.